Expatriates’ influence on knowledge sharing: an empirical study with International portuguese companies - Martins, Dora (2015)
Despite the abundant literature in knowledge management, few empirical studies have explored knowledge management in connection with international assignees. This phenomenon has a special relevance in the Portuguese context, since (a) there are no empirical studies concerning this issue that involves international Portuguese companies; (b) the national business reality is incipient as far as internationalisation is concerned, and; (c) the organisational and national culture presents characteristics that are distinctive from the most highly studied contexts (e.g., Asia, USA, Scandinavian countries, Spain, France, The Netherlands, Germany, England and Russia). We examine the role of expatriates in transfer and knowledge sharing within the Portuguese companies with operations abroad. We focus specifically on expatriates’ role on knowledge sharing connected to international Portuguese companies and our findings take into account organizational representatives’ and expatriates’ perspectives. Using a comparative case study approach, we examine how three main dimensions influence the role of expatriates in knowledge sharing among headquarters and their subsidiaries (types of international assignment, reasons for using expatriation and international assignment characteristics). Data were collected using semi‐structured interviews to 30 Portuguese repatriates and 14 organizational representatives from seven Portuguese companies. The findings suggest that the reasons that lead Portuguese companies to expatriating employees are connected to: (1) business expansion needs; (2) control of international operations and; (3) transfer and knowledge sharing. Our study also shows that Portuguese companies use international assignments in order to positively respond to the increasingly decaying domestic market in the economic areas in which they operate. Evidence also reveals that expatriation is seen as a strategy to fulfill main organizational objectives through their expatriates (e.g., business internationalization, improvement of the coordination and control level of the units/subsidiaries abroad, replication of aspects of the home base, development and incorporation of new organizational techniques and processes). We also conclude that Portuguese companies have developed an International Human Resources Management strategy, based on an ethnocentric approach, typically associated with companies in early stages of internationalization, i.e., the authority and decision making are centered in the home base. Expatriates have a central role in transmitting culture and technical knowledge from company’s headquarters to the company’s branches. Based on the findings, the article will discuss in detail the main theoretical and managerial implications. Suggestions for further research will also be presented.